Pygmalion in the courtroom: the impact of court-level racial threat on criminal justice decision making - Linnemann, Travis Wade (Kansas State University, 2006)
Building upon macrostructural “social threat” (Blalock, 1967) research, the current study develops a theoretical model of judicial decision-making processes that focuses upon racial threats perceived within individual court contexts and the corresponding effects on individual sentencing outcomes. This model recognizes that in the absence of a true-measure of a defendant’s threat to the community (likelihood to re-offend) judicial decision makers often rely upon stereotypical generalizations regarding offender populations to render decisions. Although actors develop biases and stereotypes through interactions with society in general, the most relevant knowledge affecting sentencing decisions is perceptions gained through the course of work. Similar to the influential “Pygmalion in the Classroom” study, biases and stereotypes regarding the criminality of groups of criminal defendants are pervasive in contemporary society, undoubtedly influencing sentencing outcomes. Therefore, the most meaningful measurement of threat, as it pertains to sentencing, is the contextual composition of court caseloads. Using data from the Bureau of Justice Statistics-State Court Processing Statistics (SCPS) program, this study examines court-contextual or caseload level threats and the interaction between courtroom context and individual offense/offender characteristics and the corresponding impact on sentencing outcomes. Findings demonstrate that courts of high minority defendant volume apply more punitive sanctions to (increased sentence length and odds of incarceration) to all defendants within this context, while black defendants receive the greatest sanctions. These findings support assertions regarding the impact of threatening populations within courtroom contexts.
Keywords: sentencing; racial threat; criminal justice decision making; focal concerns; court context; Sociology, Criminology and Penology (0627)